Research Progress on the Effect of Exercise and Neurobiological Mechanism on Depression - Shaokun WANG, Shiqiang WANG, Yijie WANG, Zhihan XU (Zhongguo quanke yixue, 2022)
Exercise has been confirmed by most studies to be effective in preventing and treating depression, and has become a recommended treatment by many researchers. However, previous research results on exercise interventions for depression have not been effectively integrated, and there is still a lack of uniform clinical exercise therapy guidelines across countries. In this paper, we systematically and comprehensively discussed the effects of exercise on depression, including the effects of exercise types, intensities, frequencies, and amounts of exercise on the efficacy of depression interventions in different populations, and summarized the neurobiological mechanisms involved in the development of depression as well as the antidepressant effects of exercise by sorting out relevant literature. This paper shows that in exercise interventions for depression, aerobic exercise is the most frequently chosen type of exercise, the intensity of which is usually moderate to high intensity, and the frequency and amount of exercise are recommended at high frequency and dosage. The neurobiological mechanisms of exercise resistance to depression are mainly that exercise can improve the morphological structure of central nervous system tissue, increase the levels of a series of neurotrophic factors, thereby enhancing neuronal plasticity, and improve the function of the neurosecretory system, reducing damage to brain tissue caused by neuroinflammatory responses and oxidative stress. This paper can provide a certain reference for the development and implementation of clinical exercise prescription for depression in China, and draw on the in-depth development of exercise antidepressant research.